The Relationship Between Trimester 3 Anemia Status and Chronic Energy Deficiency In Pregnant Women with Low Birth Weight Incidence - Asry Novianty; Elsa Maudi Gandirawati (Poltekkes Kemenkes Palembang, 2022)
Background Low birth weight (LBW) is a newborn whose birth weight is < 2500 grams. There are several factors that can influence the occurrence of LBW, among others, 3rd trimester anemia, chronic energy deficiency (CED), and those who experience 3rd trimester anemia and CED, and the characteristics of pregnant women. Objective This study aims to analyze the relationship between pregnant women with 3rd trimester anemia, CED and pregnant women with 3rd trimester anemia and KEK with the incidence of LBW. Methods This study uses a descriptive quantitative design. The sample of this research was taken by purposive sampling. Then in univariate analysis, bivariate analysis using Chi Square test and multivariate analysis using multiple logistic regression. Results In this study, it was found that there was a relationship between anemia in the 3rd trimester and the incidence of LBW with a p value of 0.000, there was a significant relationship between pregnant women who experienced CED and the incidence of LBW with a p value of 0.000. However, there is no relationship between pregnant women who experience third trimester anemia and CED simultaneously with the incidence of LBW. From the characteristics of pregnant women, there is a relationship between the age of pregnant women with the incidence of LBW with a p value of 0.043 and the gestational age with the incidence of LBW with a p value of 0.01. Conclusion From this study, it was concluded that there are 4 factors that influence the occurrence of LBW, which are third trimester anemia, CED, maternal age and gestational age.